Factors predicting major complications, mortality, and recovery in percutaneous endoscopic gastrostomy. Issue 5 (31st March 2021) - Limpias Kamiya, Kenji J L; Hosoe, Naoki; Takabayashi, Kaoru; Hayashi, Yukie; Fukuhara, Seiichiro; Mutaguchi, Makoto; Nakamura, Rieko; Kawakubo, Hirofumi; Kitagawa, Yuko; Ogata, Haruhiko; Kanai, Takanori
Abstract: Background and Aim: Percutaneous endoscopic gastrostomy (PEG) has been used in patients with dysphagia and inadequate food intake via an oral route. Despite being a procedure with a high success rate, complications and death have been reported. The aim was to identify the factors related to major complications and mortality, as well as PEG removal prognostic factors due to improvement of their general condition. Methods: Patient characteristics, comorbidities, laboratory data, concomitant medication, sedation, and indication for PEG placement were collected. Major complications, mortality, and PEG removal factors were assessed. Results: A total of 388 patients were enrolled. There were 15 (3.9%) cases of major complications, with major bleeding being the most frequent in 6 (1.5%) patients. Corticosteroids were the independent variable associated with major complications (odds ratio [OR] 5.85; 95% confidence interval [CI] 1.71–20; P = <0.01). Advanced cancer (hazard ratio [HR] 0.5; 95% CI 0.3–1; P = 0.05), albumin (HR 0.6; 95% CI 0.4–0.9; P = <0.01), and C‐reactive protein (CRP) (HR 1.1; CI 1–1.2; P = 0.01) were considered risk factors for mortality. Previous pneumonia (HR 0.4; CI 0.2–0.9; P = 0.02) was a factor for permanent use of a PEG; however, oncological indication (HR 8.2; CI 3.2–21; P = <0.01) was factors for PEG withdrawal. Conclusions: Chronic corticosteroid users potentially present with major complications. Low albumin levels and elevated CRP were associated with death. Previous aspiration pneumonia was a factor associated with permanent use of PEG; however, patients with oncological indication were the most benefited. Abstract : Chronic corticosteroid users potentially a risk factor for major complications after percutaneous endoscopic gastrostomy (PEG) placement. Previous history of aspiration pneumonia was a factor associated with permanent use of PEG. Prophylactic PEG tube feeding in patients with oncological indication was the most benefited in achieving recovery.